2019
DOI: 10.1007/s11684-019-0682-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth suppression of colorectal cancer expressing S492R EGFR by monoclonal antibody CH12

Abstract: Colorectal cancer (CRC) is a common malignant tumor in the digestive tract, and 30%-85% of CRCs express epidermal growth factor receptors (EGFRs). Recently, treatments using cetuximab, also named C225, an anti-EGFR monoclonal antibody, for CRC have been demonstrated to cause an S492R mutation in EGFR. However, little is known about the biological function of S492R EGFR. Therefore, we attempted to elucidate its biological function in CRC cells and explore new treatment strategies for this mutant form. Our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…L688F and E690K were in exon 18 and K754E in exon 19, which is in contrast to others responsive to lapatinib treatment (Leslie et al, 2013;Reyes et al, 2014) Colorectal cancer: EGFR mutation status of 13 patients among 35 male and 23 female patients at different stages of colorectal cancer showed exon 20 mutation but not exons 18,19 and 21 mutations (Oh et al, 2011). S492R EGFR ectodomain mutation also increases the mutation rate and mABCH12 was suggested to prevent the effect of mutated EGFR (Dong et al, 2019).…”
Section: Homologymentioning
confidence: 82%
“…L688F and E690K were in exon 18 and K754E in exon 19, which is in contrast to others responsive to lapatinib treatment (Leslie et al, 2013;Reyes et al, 2014) Colorectal cancer: EGFR mutation status of 13 patients among 35 male and 23 female patients at different stages of colorectal cancer showed exon 20 mutation but not exons 18,19 and 21 mutations (Oh et al, 2011). S492R EGFR ectodomain mutation also increases the mutation rate and mABCH12 was suggested to prevent the effect of mutated EGFR (Dong et al, 2019).…”
Section: Homologymentioning
confidence: 82%
“…42 Amplifications are notably more prevalent in Chinese populations; around 14% of patients with KRAS/BRAF WT mCRC and 4.4% with RAS mutant disease. 43 An analysis of patients from the "FOCUS" and "PICCOLO" studies (n=1342) in mCRC demonstrated that Her2 amplification confers resistance to anti-EGFR treatment. 42,44 Her2 activating mutations, which are also rare in breast and gastric cancer, are found in around 2% of mCRC; these will not be identified by immunohistochemistry.…”
Section: Targeting Her2mentioning
confidence: 99%